THE DEPICTION OF REPRESSION TRIGGERED BY TRAUMA OF BONE CHARACTER IN DOROTHY ALLISON'S BASTARD OUT OF CAROLINE - ORIZA PRASTY LESTARI, 121411223011 (2016)
This study examines the issue of defense mechanism used in Dorothy Allison’s novel Bastard Out of Carolina. The study focusses on Bone, the main character in Bastard Out of Carolina in coping her trauma using repression as defense mechanism. Trauma and defense mechanism have been closely related to each other in psychological aspect. To examine Bone’s personality, the writer applies the term of trauma and repression as defense mechanism which are introduced by Sigmund Freud’s psychoanalysis concept. This study reveals that Bone’s anxiety is resulted from her childhood trauma being abused sexually, being left by the death of her beloved persons, and also being an illegitimate child. Moreover, the study is also focused on the psychosexual stages, anxiety, and trauma faced by Bone. The study is conducted using qualitative method which emphasizes Bastard Out of Carolina as the primary source, and also article journal, encyclopedia as the secondary sources. The aim of this study is to reveal the function of repression as defense mechanism done by the main character through the novel. In the end of the study, the writer depicts the function of defense mechanism in coping Bone’s trauma in life. The finding also shows that Bone can cope her trauma as well by using repression as her defense mechanism.